SLAFRAMINE INTOXICATION IN HORSE IN SANTA CATARINA STATE - Fonteque, Joandes Henrique; Souza, Anderson Fernando; Schade, Jackson; Muller, Thiago Rinaldi; Weinert, Nádia Cristine (Veterinária e Zootecnia, 2022)
A case of slaframine toxicosis has been reported in a seven year-old, half-breed horse weighing 400Kg, used for traction. The animal demonstrated excessive salivation as the clinical sign and it was maintained on a pasture with red clover (Trifolium pratense). Upon the inspection of the pasture, observed leaves changes compatible with infection by Rhizoctonia leguminicola. The suspicion was slaframine toxicosis, removal of the animal from the pasture with clover was indicated as treatment. The clinical sign stopped 24h after the feed had been withdrawn confirming the therapeutic diagnosis.